‘Fine specimens of the race’ : Pourquoi se porte-t-on si bien dans Nouvelles de Nulle Part ? - Nathalie Saudo (Revue Française de Civilisation Britannique)
Good health is a necessary feature of utopias. In News from Nowhere, this theme takes on a particular importance. While drawing comparisons with some of William Morris’s sources, this article shows that his description of healthy bodies constitutes a response to some contemporary discourses (social Darwinism, the ideology of degeneration, public hygiene and ‘The Condition of England’) and that the association between health and wealth is central to his political thought.